BIM technology in geotechnical engineering in terms of impact high building "Mogilska Tower" in Cracow of existing building development - Szwarkowski, Dariusz; Pilecka, Elżbieta (Technical Sciences, 2017)
The article presents the use of BIM design method in geotechnical issues. BIM was used in the modeling of high building “Mogilska Tower” in Cracow. The object, as one of the few in Cracow, will have three underground storeys. High building with underground levels requires checking the impact of the implementation of a deep excavation on existing buildings. Analysis of settlement impact caused by deep excavation and the planned load of the building is based on the guidelines contained in the ITB (KOTLICKI, WYSOKIŃSKI 2002) standards by the simplified method and detailed method determined on the basis of numerical analysis. The article presents the results of the vertical deformation of ground adjacent to the existing object. The results of the calculations were compared with the limit values shown in ITB and PN-81/B-03020 (1985). Numerical analysis was performed in the spatial state of stress and strain model. It takes into account the spatial layout of the geotechnical subgrade and the terrain shape obtained by the measurement of terrestrial laser scanner. Subgrade was modeled elastic-plastic model of Mohr-Coulomb with linear condition of plasticity. Identified the influence and range of deep excavation and loads of the planned high building on existing development.